PENGATURAN PENGKAPLINGAN TANAH UNTUK PERUMAHAN DI KABUPATEN TABANAN - Striratna, Adina; Putra Ariana, I Gede (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
The paper shall be entitled as Land Plot Regulatory Framework for HousingMeans in Tabanan Regency. This writing uses normative legal research combined withstatutory approach. This writing shall illustrate the absence of norms towards theregulation of land plot in Tabanan. Regent of Tabanan had enacted the Regency DecreeNo 673 of 2002 concerning Implementative Regulation of Land Plot in Tabanan. Thiswriting aims to unveil the procedure of land plot and its supervising mechanism by theauthorized government official pursuant to Regency Decree. Thus, such decree shallallow the permit of land usage in order to prevent the absence of norms in the means ofland plot.
Keywords: Regulation, Permission, Land Plot